Budaya Mencontek di Sekolah: Analisis Kasus Literasi dan Dampaknya Terhadap Proses Pembelajaran dan Etika Akademik - Vadila Zikra Rahma; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
Cheating culture among school students has long been a disturbing phenomenon threatening academic integrity. This research aims to analyze the factors influencing the prevalence of the cheating culture in schools and its impact on the learning process and academic ethics. Through a comprehensive literature review, this study identifies academic pressure, lack of interest in the material, and insufficient emphasis on academic integrity as key factors causing cheating. The impacts include weakened understanding of the material, reduced intrinsic motivation, and the risk of developing unethical attitudes. The research recommends a holistic approach involving curriculum changes, improved engaging teaching methods, and active roles for teachers, parents, and students in creating a supportive and ethical learning environment. Visual data in the form of graphs and diagrams provide a clear overview of the prevalence and patterns of cheating behavior in elementary schools, serving as a foundation for the development of effective prevention and intervention strategies. Thus, this research is expected to make a significant contribution to understanding and addressing the cheating culture to create a fair and dignified educational environment.